Design dan Penerapan SD WAN Pada PT Rafalsindo menggunakan Metode Dynamic Multi-Path optimization (DMPO) - Ahmad Rais Ruli; Rio Wirawan (Prosiding Seminar Nasional Teknoka, 2020)
SD-WAN is a software defined network in a wide area network (WAN). SD-WAN simplifies WAN management and operation by separating network hardware from its control procedures. This concept is similar to how software-defined networks apply virtualization technology to improve data center management and operations.The primary application of SD-WAN is to enable enterprises to build higher-performance WANs using low-cost and commercially available Internet access, enabling businesses to partially or entirely replacing more expensive private WAN connection technologies such as MPLS. As information before, PT Rafalsindo used MPLS (Multi Protocol Cap Switching) which now looks expensive leasing paths where PT Rafalsindo has several sites on Java Island, with SD-WAN being selected this utilizes programmable Skills that are flexible network determined by software To provide jpath jpath routing and perform traffic control to reduce network costs by offloading traffic from expensive rental spathes to the public internet, in this implementation the author uses the Dynamic Multi-Path Optimization (DMPO) method, where Dynamic Multi-Path Optimization (DMPO) is a combination of dedicated internet networks, broadband Internet, 4G-LTE, and MPLS with application-aware link directing per Delivery and on-demand remediation to offer the best performance for real-time voice and video requests via any transport. is a special Internet Network Combined, Int ernet broadband, 4G-LTE, and MPLS with application-aware per-packet link referrers and on-demand remediation to achieve optimal performance